Performing site-specific theatre : politics, place, practice - Birch, Anna; Tompkins, Joanne (Performance interventions., 2012)
Performing Site-Specific Theatre' turns a critical eye to the increasingly popular form of site-specific performance. By re-assessing this contemporary practice, the book investigates the nature of the relationship between 'site' and 'performance.' Site-specific performance operates differently from performance that takes place within a theatre venue because it seeks to match form and content (and place and space) more finely than does theatre that takes place inside conventional venues. Yet the form also encourages an investigation of how we might understand 'site' as less fixed or less specifically geographical; it broadens the types of relevant 'spaces' we might consider. The form also enables us to address a range of performative issues, from the development of site-specific 'soundscapes' to the role of the spectator in site-specific performance.